2001
DOI: 10.1038/sj.ejcn.1601121
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between stunting in infancy and growth and fat distribution during adolescence in Senegalese girls

Abstract: Objective: To study the long-term impact of stunting during infancy on maturation, growth and fat distribution in adolescence. Design: A cohort of 406 Senegalese adolescent girls of rural origin underwent clinical and growth assessments every year from 1995 to 1999. Subjects: Mean coverage rate was 82% at each round. Adolescent girls were 11.4 AE 0.5 y of age in 1995 and 15.5 AE 0.5 y of age in 1999. Their growth status during infancy was known. About 20% of the girls had a height ± age (H ± age) below À2 Z-sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
1
13

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 25 publications
6
44
1
13
Order By: Relevance
“…17 This tendency for stunted girls to catch up in body fat was also reported in Senegalese girls at age 11-15 years. 11 However, in neither study was there any evidence that stunted girls became fatter than those who were never stunted.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…17 This tendency for stunted girls to catch up in body fat was also reported in Senegalese girls at age 11-15 years. 11 However, in neither study was there any evidence that stunted girls became fatter than those who were never stunted.…”
Section: Discussionmentioning
confidence: 77%
“…We previously reported that stunted children identified at age 9-24 months remained thinner at age 11 years than non-stunted children from the same neighborhoods. 10 A study of girls aged 11-15 years in Senegal found no difference in body mass index (BMI) or body fat between those stunted or non-stunted in infancy, 11 suggesting some catch-up in weight in the stunted group as they were thinner in infancy. Follow-up of Guatemalan children showed that childhood stunting was associated with lower BMI and body fat among men at age 18-24 years but no relation was found in women.…”
Section: Introductionmentioning
confidence: 99%
“…Measurements were taken in duplicate and were averaged to minimize the variance. Interand intraobserver coefficients of variation were low (Bénéfice et al, 2001b).…”
Section: Measurementsmentioning
confidence: 82%
“…Since 1995, our group has been performing a follow-up study on growth and maturation throughout puberty in a sample of approximately 390 adolescents, including almost all the girls in the district of Niakhar (Center of Senegal) born in 1983 and 1984 (Bénéfice et al, 2001b). We hypothesized that growth and maturation delays observed in these adolescent girls were linked to high daily energy expenditure due to an excessive workload that may create competition between familial and social pressure to work, and the satisfaction of their nutritional and energy needs.…”
Section: Study Areamentioning
confidence: 99%
“…Isso porque os eventos da puberdade relacionam--se ao estado nutricional, especialmente ao perfil de composição corporal e, portanto, esse aspecto constitui um potencial fator de confusão 25 .…”
Section: I S C U S S ã Ounclassified